1880 Ohio Rev. Stat. 1633, tit. 1, ch. 5, § 6892 (vol. 2, 1879) - (:unkn) unknown (My University, 1880)
Prohibited the concealed carrying of any pistol, Bowie knife, dirk, or other dangerous weapon. Punishable by a fine of up to $200 or imprisonment for up to 30 days for the first offense, and a fine of up to $500 or imprisonment for up to 3 months for the second offense.
Keywords: CARRY - CONCEALED